Foodborne Illness Outbreak Investigation Amongst Party Guests in Highfield Suburb, Harare City, Zimbabwe, 2020: A Retrospective Cohort Study - Linda Nyasha Kanzara; Portia Manangazira; Emmanuel Govha; Tsitsi Patience Juru; Addmore Chadambuka; Notion Tafara Gombe; Maurice Omondi; Mufuta Tshimanga (Journal of Interventional Epidemiology and Public Health)
Background: On November 2, 2020, 5 patients presented at Highfield Polyclinic with fever, diarrhoea, abdominal pain, vomiting and some with dehydration after attending the same party on October 31, 2020. We aimed to determine the factors associated with this outbreak and identify a possible etiological agent.